SERAPAN FOSFOR TANAMAN TERHADAP PEMBERIAN MIKORIZA ARBUSKULA DI BEBERAPA JENIS RUMPUT TERHADAP DERAJAT MIKORIZA - Rahmaniah Rahmaniah; Roswita Oesman (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
It is hoped that mycorrhiza will increase plant P uptake, and the degree of infection (%) of roots in ultisol soil and the application of arbuscular mycorrhizal fungi to various animal feeds is to determine the effect of mycorrhizal and phosphorus (P) uptake on plants so that the degree of mycorrhizal and phosphorus (P) absorption by plants is affected. . This research was conducted from March 2022 to October 2022 on the land of the Faculty of Agriculture, University of Community Development. This design uses a completely randomized design consisting of two factors. The first factor was the type of grass used consisting of Paspalum guenarum (P1), Paspalum notatum (P2), Brachiaria ruziziensis (P3), Brachiaria humidicola (P4), and Panicum maximum (P5). The second factor was the microsphere level which consisted of 0 gr (M0), 10gr (M1), 20gr (M2) and 30gr (M3). Research Results Mycorrhiza increased plant P uptake, and root infection degree (%) in ultisol soil Arbuscular mycorrhizall Fungi (MVA) administration at a dose of 30 g/polybag showed the best results in response to root infection degree a plant phosphorusrus uptake